Positive affect, negative affect, and psychological resilience mediate the effect of self-compassion on mental toughness: A serial mediation analysis - Eryilmaz, Ali; Yildirim-Kurtulus, Hacer; Doenyas, Ceymi (WILEY, 2023)
Following the positive youth development perspective that emphasizes the importance of focusing on the positive assets of youth to be developed, this study examined the variables related with mental toughness, a trainable skill that is associated with psychological and academic well-being outcomes, in preadolescent youth. The effect of self-compassion on the mental toughness of preadolescents and the serial mediating effect of positive/negative affect and psychological resilience was explored for the first time in the literature to the best of our knowledge, via the causal-comparative model. The study group consisted of a total of 263 preadolescents (ages 10-13). The results show that self-compassion increases positive affect and this increases the mental toughness of preadolescents. As negative affect is negatively associated with mental toughness, by decreasing negative affect, self-compassion positively influences mental toughness. Alternately, self-compassion increases resilience, which in turn increases mental toughness. The findings of this study indicate that positive/negative affect and resilience play a serial mediating role in the relationship between self-compassion and mental toughness. These relationships highlight the components to be included in interventions directed toward adolescents to improve the trainable skill of mental toughness, which can then lead to positive well-being outcomes concurrently and through adulthood.
Keywords: adolescence; mental toughness; positive; negative affect; resilience; self-compassion; YOUNG-CHILDREN; ADOLESCENTS; YOUTH; PERFORMANCE; VALIDATION; EMOTIONS; BROADEN; ESTEEM; HEALTH; ADULTS; Psychology